Phylogenetic Analysis of Streptomyces spp. Exhibited Different Antimicrobial Activities - Al-Rubaye, Dalal S. (Iraqi Journal of Science, 2023)
Fourteen isolates were collected from a previous study and all were assigned to be Streptomyces genus, according to physiological and biochemical tests, however all the isolates varied morphologically and exhibited different antimicrobial activity. All 14 isolates were confirmed Streptomyces by 16S rRNA PCR amplification. Six isolates with high antimicrobial activities were ascertained Streptomyces spp. by sequencing and phylogenetic analysis. Two isolates among the selected 6 isolates with antimicrobial activity against E. coli and S. aureus . It recommended to make a complete sequence for 16S rRNA to detect the species that produce antimicrobial substances, also it’s very necessary to identify the natural structure of these product.